Factors Affecting Consumer Decisions In Purchasing Oppo Handphones In The City Of Manna Bengkulu Selatan - Lorenza Aprilia; Neri Susanti; Yudi Irawan Abi (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
The purpose of this research was to determine the factors that influence consumer decisions in purchasing oppo cellphones in the city of Manna, South Bengkulu. Methods of data collection is done by distributing questionnaires. While the analytical methods in this study are validity test, reliability test, multiple linear regression and hypothesis testing. The results of linear regression calculations show Y = 6.776 + 0.388X1 + 0.402X2. These results describe a positive regression direction, this means that there is a positive or significant influence between word of mouth (X1) and lifestyle (X2) on purchasing decisions (Y). The coefficient of determination is 0.664 or 66%, this indicates that the dependent variable (purchasing decision) can be explained by the independent variables (word of mouth and lifestyle) influencing purchasing decisions by 66%, while the remaining 34% purchasing decisions are influenced by other variables that are not included in this research model. From the F test obtained a significance value of 0.000 <0.05, which indicates that together X1 (Word of mouth), and X2 (Lifestyle), have a simultaneous significant influence on Purchase Decision (Y). Meanwhile, word of mouth partially influences the decision to buy oppo cellphones with a probability value (Sig) 0.014 <0.05, lifestyle influences purchasing decisions for oppo cellphones with a probability value (Sig) 0.006 <0.05.